The effect of lidocaine spray use on patients comfort in undergoing urinary catheterization: A prospective, observational, Randomized Control Trial - Celikel, Elif; Erdem, Ahmet Burak; Sarcan, Emine; Kuzucu, Burak Burhan; Alp Sener; Gulhan Kurtoglu Celik (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the efficacy of applying lidocaine spray in improving patient compliance and comfort relate to urinary catheterisation. Method: The prospective, case-control study was conducted at Ankara City Hospital und Etlik City Hospital from July 1, 2022, to December 1, 2023, and comprised adult male patients with spontaneous micturition undergoing urinary catheterisation in the emergency department. They were randomised into lidocaine Group L and control Group P. Pain levels were evaluated at 0 minute coinciding with the initiation of the procedure, as well as 15, 30 and 60 minutes afterwards. The Face-Legs-Arms-Cry-Consolability Scale and Wong-Baker pain scales were used. Data was analysed using SPSS 20. Results: Of the 200 patients, 100 patients were in Group L with median age 68.5 years (interquartile range: 53.5-77.5 years) and 100 patients were in Group P with median age 73.0 years (interquartile range: 63.5-79.5 years) (p=0.031). The pain scores at all time periods in Group L were significantly lower thab Group P (p<0.05). All Face-Legs-Arms-Cry-Consolability-Pain Scale scores were significantly higher in Group P than in Group L (p<0.05). Conclusion: Lidocaine spray could reduce pain during urinary catheterisation and increase patient comfort. Clinical trial number: NTC06585748. Key Words: Urinary catheterisation, Pain control, Lidocaine spray, Patient comfort.